Revolusi pendidikan: Mengoptimalkan potensi dengan Kurikulum Merdeka - Shofi, Ajmal Ramzani Nasywa (Maliki Interdisciplinary Journal, 2024)
The Merdeka Curriculum is the latest initiative in Indonesian education designed to provide freedom and flexibility to students and teachers in the learning process. This abstract discusses how the Merdeka Curriculum aims to optimize the potential of each student with a more personal approach and relevant to the needs of the times. Through more interactive and contextual learning methods, students are encouraged to be more creative, critical, and independent. This curriculum also provides space for teachers to develop material that suits students’ interests and talents, so that the teaching and learning process becomes more dynamic and fun. This article will review various aspects and benefits of the Merdeka Curriculum, as well as the challenges faced in its implementation in the field. By understanding the essence of the Merdeka Curriculum, it is hoped that educators, students, and parents can jointly create a better, innovative, and adaptive learning environment to changing times.